Lapped Orthogonal Vector Quantization - Malvar, Henrique S.; Sullivan, Gary J.; Wornell, Gregory W. (Data Compresison Conference, 1996)
The blocking artifacts that arise in the use of traditional vector quantization (VQ) schemes can, in general, be virtually eliminated via an efficient lapped VQ strategy. With lapped VQ, blocks are obtained from the source in an overlapped manner, and reconstructed via superposition of overlapped codevectors. The new scheme, which we term lapped orthogonal vector quantization (LOVQ), requires no increase in bit rate and, in contrast to other requirements. Attractively, the use of LOVQ also leads to a modest increase in coding gain over traditional VQ schemes of comparable complexity.